Freestanding VO2 membranes on epidermal nanomesh for ultra-sensitive correlated breathable sensors - Dongha Kim; Dongju Lee; Jiseok Park; Jihoon Bae; Aiping Chen; Judith L. MacManus-Driscoll; Sungwon Lee; Shinbuhm Lee (Nano Convergence)
Abstract The interest in highly sensitive sensors is rapidly increasing for detecting very tiny signals for Internet of Things devices. Here, we achieve ultra-sensitive correlated breathable sensors based on freestanding VO2 membranes. We fabricate the membranes by growing VO2 films onto sacrificial Sr3Al2O6 layer grown on SrTiO3, selectively dissolving the Sr3Al2O6 in water, and then rendering freestanding VO2 membrane on nanomesh. The nanomeshes are extremely flexible, sweat permeable, and readily skin-adhesive. The resistance of the VO2 membranes is reversibly tuned by human’s tiny mechanical stimuli and breath stimuli. The stimuli modulate the Peierls dimerization of one-dimensional V−V chains in the VO2 lattice which concomitantly controls the electron correlation and hence resistivity. Since our breathable sensors operate based on quantum-mechanical correlation effects, their sensitivity is 1−2 orders of magnitude higher than conventional tactile and respiratory sensors based on other materials. Thus, the freestanding membranes of correlated oxides on epidermal nanomeshes are multifunctional platforms for developing ultra-sensitive correlated breathable sensors. Graphical Abstract